Alpha-Glycerylphosphorylcholine and D-Panthenol Eye Drops in Patients Undergoing Cataract Surgery. (7th June 2022) - Martone, Gianluca; Balestrazzi, Alessandra; Ciprandi, Giorgio; Balestrazzi, Angelo
Abstract : Cataract surgery is widespread. The surgical procedure is associated with damage to the epithelial barrier and interruption of the corneal innervation. In addition, pathological events sustain signs and symptoms that may persist for a long time. Recently, a fixed combination of alpha-glycerylphosphorylcholine and D-Panthenol (Oftassiale) has been available as eye drops. The present study investigated the effects of an Oftassiale therapy in 20 patients undergoing cataract surgery. A comparison group included 20 patients treated with topical hyaluronic acid. Standard prophylactic and anti-inflammatory treatment was prescribed to all patients. Clinical signs and symptoms were assessed over time. In vivo confocal microscopy (IVCM) was performed accordingly. Oftassiale treatment significantly reduced clinical features and improved IVCM outcomes. In addition, therapy was well-tolerated, and no clinically significant adverse events occurred. In conclusion, this study confirmed that IVCM helps assess the tunnel after cataract surgery due to its ability to provide microscopic details in vivo. Topical therapy with alpha-glycerylphosphorylcholine and D-Panthenol eye drops promoted and stabilized the reepithelialization process. This fixed combination also accelerated and modulated the repair of the corneal innervation. Moreover, this treatment was well-tolerated and safe.